A thin‐film transistor with no apparent channel for simplified, high aperture ratio pixel architectures. Issue 10 (14th June 2022) - Wilson, Joshua; Zhang, Jiawei; Song, Aimin
Abstract: Advances in practical electronics often result from the quest to improve the scalability of fundamental components, but improvements in the scalability of thin‐film transistors (TFTs) have been frustrated by performance degradation at reduced dimensions. In particular, many of these scaling issues are tied to a common feature of all transistors, the semiconductor channel. Here, we introduce TFTs with source and drain materials in direct contact. In the absence of a channel, these TFTs maintain excellent performance including high effective mobility and low voltage saturation. Central to our design is the combination of the depleting properties of a Schottky source electrode with a quasi‐metallic drain material, in this case indium‐tin‐oxide. As an example application, we propose a simpler, more compact pixel architecture for realizing high‐resolution displays, which reduces transistor area by two thirds and can reduce pixel power consumption by almost 80% when compared to conventional TFT structures. Abstract : Creating and controlling a Schottky barrier at the source contact of a thin‐film transistor removes the need for a gate‐modulated semiconductor channel. Without a channel, these "source‐gated transistors" (SGTs) exhibit excellent performance, including high effective mobility and low voltage saturation. Owing to the reduced area of the new SGT structure, a simple, compact, high aspect ratio pixel architecture is devised.